Multimedia environmental models : the fugacity approach - Mackay, Donald, 1936-; Parnis, J. Mark (Boca Raton, FL : CRC Press, 2021)
Multimedia Environmental Models: The Fugacity Approach, Third Edition, takes a broad approach of viewing chemical behavior in the total biosphere of connected biotic and abiotic compartments. Chemicals are subject to the laws of "mass balance," a constraint that provides the opportunity to establish quantitative expressions for chemical fate that are central to chemical management and regulatory legislation. This book employs both the conventional concentration-based procedures and those based on application of the more elegant and powerful concept of fugacity to characterize equilibrium, steady-state distribution, and time-dependent transport between environmental phases such as air, water, and soil. Organic chemicals are emphasized because they are more easily generalized when assessing environmental behavior. Features Illustrates professional approaches to calculating the fate of chemicals in the environment Explicitly details all worked examples in an annotated step-by-step fashion Presents real-life freely downloadable models of use to government, industry, and private consulting professionals and students alike Clarifies symbols and notation.
OCLC-licensed vendor bibliographic record.
Keywords: Organic compounds -- Environmental aspects -- Mathematical models; Cross-media pollution -- Mathematical models; SCIENCE / Chemistry / General